Risk Neutrality and the Two-Tier Foreign Exchange Market : Evidence from Belgium. (IMF Working Papers; Working Paper ;, 1989)
In this paper we develop and test a model of a utility maximizing representative agent operating in the Belgium-Luxembourg two-tier foreign exchange market. Our tests examine and fail to reject a risk neutral representative agent utility function. When we combine a risk neutral utility function with goods arbitrage we end up with the implication that the proportionate spread between the current account and financial exchange rates is not influenced by domestic policy. This implication is not rejected in some additional tests relating the Belgium-Luxembourg two-tier market: spread to some Belgian policy variables and some foreign variables.